Effect of Electromagnetic Fields on Microbial Activity of a Bio-Fertilizer - Zuñiga, Orlando; Jiménez, Cristian; Benavides, Jhony; Torres González, Celina (Revista de Ciencias, 2016)
The  level  of  microbial  activity  was  evaluated  in  an  organic  substrate  and  over  soil  samples  from  the  “El  Limonar”  county  (Dagua,  Valle  del  Cauca)  to  which  it  was  applied  the  commercial bio-fertilizer Multibiol electromagnetically stimulated. Phase i of the experiment was conducted to determinate the best times of exposure and electromagnetic induction on the bio-fertilizaer applied to samples of an organic substrate (chicken manure).